UJI ANTIBAKTERI DAN FORMULASI SEDIAAN MASKER ANTI JERAWAT YANG MENGANDUNG KAYU MANIS (Cinnamomum burmanni Nees &T. Nees ) - Oom Komala; Ella Noorlaela; Andhika Dhiasmi (EKOLOGIA, 2018)
Cinnamon contains eugenol and cinnamaldehyde compounds and is widely used as an anti acne. The aim of this research make cinnamon maskers which has antibacterial power of Staphylococus aureus, to know the effect of cinnamon maskers storage to quality, and know Cinnamomum burmanii maskers prefered by panelist. Cinnamon extract is made by maceration method, Test the antibacterial activity of maskers by diffusion method. The evaluation of maskers is done stability test at room temperature (25oC-30oC) and temperature 40oC for 8 weeks, and test prefered by panelists. Cinnamon extract maskers is made with various concentrations of formula 1 with cinnamon extract 0%, formula 2 with 8% concentration, formula 3 with 10% concentration and formula 4 with 12% concentration, and tetracycline is control. The results of the study were known maskers with cinnamon 12% concentration most effective as an antibacterial with average of 16 mm diameter and most preferred, stable at room temperature 25oC-30oC and 40oC for 8 weeks. pH of Maskers ranges from 5.31 to 6.89 which is still the normal range for pH of the preparation.Key words: Pandan fragrance, Streptococcus mutans, mouthwash